The Effect of Firm Size, Dividend Yield, Earning Per Share and Net Profit Margin on Stock Prices in Pharmacy Companies Listed on the Indonesia Stock Exchange for the 2017-2022 Period - Ramadhani, Septi Mariani Tis’a; Ekanova, Angga Putri; Anwar , Chika Silvia (Journal of Comprehensive Science, 2024)
Pharmaceutical companies are companies listed on the Indonesia Stock Exchange (IDX) which are said to be important, especially during the Covid-19 pandemic because they can provide medicines and medical devices so that the demand for medicines will increase. This trend has resulted in investors who still want to invest during a pandemic, preferring pharmaceutical companies to buy the stock, thus causing stock prices to change. The purpose of this research is to determine the effect of firm Size, Dividend Yield, Earning Per Share and Net Profit Margin on Stock Prices in Pharmaceutical Companies Listed on the IDX for the 2017-2022 period. The population in this research are 11 pharmaceutical companies listed on the IDX in the 2017-2022 period. The samples taken in this research are 5 companies. The sampling technique used is purposive sampling. The data used is secondary data in the form of annual financial reports. The data analysis techniques used are the normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression analysis, F test, t test and R2. The test instrument used is SPSS. The results of this research indicate that partially and simultaneously, the variables Firm Size, Dividend Yield, Earning Per Share and Net Profit Margin affect stock prices in pharmaceutical companies listed on the Indonesia Stock Exchange for the 2017-2022 period.